Analysis Of The Prohibition On Advertising In The Code Of Ethics Of The Advocate Profession - Fauziah Lubis; Rofitrah Fadli Sihombing; Sayyidah Aqillah H; Rodhiatun Mardiah; Nurliana, Nurliana; Parhan Azmi (SEAN Institute, 2025)
The purpose of this study is to analyze the factors that cause violations of the code of ethics committed by an advocate so that in exercising his authority he can act in accordance with applicable moral and professional standards. Every professional profession has moral principles that are regulated in a code of ethics, including advocates. The application of the code of ethics in the Advocate profession is very important because it is used as a form of moral resilience for the Advocate profession. In reality, the implementation of law in the field there are still advocates who violate the advocate code of ethics. This research aims to analyze the code of ethics applied by the advocate profession so that in exercising its authority it can act in accordance with applicable moral and professional standards. This research uses qualitative methods with library research techniques emphasizing sources of information from law books, journals and papers that have a relevant relationship with the title discussed. The results obtained ideally professional ethics is a regulator of law enforcement behavior as part of efforts to realize good and fair law enforcement. The advocate's code of ethics as a juridical basis in carrying out the profession acts to guarantee and provide protection to advocates from deviant actions, although on the other hand humanity certainly imposes a great responsibility for an advocate in carrying out his profession. Advocates have a code of ethics which is regulated in the articles in the Indonesian Advocates Code of Ethics (KEAI) 2002. Advocates also have a supervisory board formed by the advocate organization and is authorized to oversee the implementation of the professional code of ethics